The history of the middle in Dogon - Christopher Culy; Sarah M.B. Fagan (Studies in African Linguistics, 2001)
Donno So, a Dogon language of Mali, has a class of verbs (C3) that exhibits an interesting set of formal and semantic properties. The verbs in this class have different derivational histories; they also have various typs of meaning (middle; middle-related; non-middle). Although C3 verbs cannot be unified derivationally or semantically, they can all be defined both paradigmatically and in terms of phonotactic constraints, like the other two verb classes in Donno So. Comparison with other Dogon languages shows how the middle evolved in Dogon and how Donno So C3 verbs in turn evolved from the middle. These results expand Kemmer's [1993] discussion of the processes invoved in the evolution of middle systems. The comparison also provides some hypotheses about the history of Dogon.